Bioassay-Guided Isolation of Neuroprotective Compounds from Uncaria rhynchophylla against Beta-Amyloid-Induced Neurotoxicity - Xian, Yan-Fang (Hindawi Publishing Corporation, 2012)
Uncaria rhynchophylla is a component herb of many Chinese herbal formulae for the treatment of neurodegenerative diseases. Previous study in our laboratory has demonstrated that an ethanol extract of Uncaria rhynchophylla ameliorated cognitive deficits in a mouse model of Alzheimer's disease induced by D-galactose. However, the active ingredients of Uncaria rhynchophylla responsible for the anti-Alzheimer's disease activity have not been identified. This study aims to identify the active ingredients of Uncaria rhynchophylla by a bioassay-guided fractionation approach and explore the acting mechanism of these active ingredients by using a well-established cellular model of Alzheimer's disease, beta-amyloid- (Aβ-) induced neurotoxicity in PC12 cells. The results showed that six alkaloids, namely, corynoxine, corynoxine B, corynoxeine, isorhynchophylline, isocorynoxeine, and rhynchophylline were isolated from the extract of Uncaria rhynchophylla. Among them, rhynchophylline and isorhynchophylline significantly decreased Aβ-induced cell death, intracellular calcium overloading, and tau protein hyperphosphorylation in PC12 cells. These results suggest that rhynchophylline and isorhynchophylline are the major active ingredients responsible for the protective action of Uncaria rhynchophylla against Aβ-induced neuronal toxicity, and their neuroprotective effect may be mediated, at least in part, by inhibiting intracellular calcium overloading and tau protein hyperphosphorylation.